Peran Brosur Digital Sebagai Media Promosi dalam Penerimaan Peserta Didik Baru di Sekolah IB Medan - Dinda Ayu Lestari br Ginting; Dedi Sahputra (Journal of Education, Humaniora and Social Sciences (JEHSS), 2025)
This study examines the role of digital brochures as a promotional media for new student admissions at Integritas Bangsa (IB) School in Medan, its impact on the education competition in Medan, and the challenges faced in marketing using this medium. The main focus of the problem is how digital brochures serve as a promotional tool to attract new students. This study uses a marketing communication approach, the uses and gratifications theory, with a qualitative descriptive method. Data collection techniques include observation, in-depth interviews, and literature studies, while data analysis follows the Huberman and Miles model, which includes data reduction, data presentation, and conclusion drawing. The results show that digital brochures are effective in promoting new student admissions at IB School in Medan, with advantages in cost efficiency, flexibility, and wide reach. The main challenges include the limitations of parents who are not familiar with technology and the competition on social media. To address this, the school innovates with brochure formats and interactive promotions. Parental feedback encourages improvements, and regular evaluations ensure the effectiveness of the digital marketing strategy.